An equation with no solution is one that simplifies to a contradictory statement. Let's analyze each option:
-
3x + 4 = 4x + 3
- Rearranging gives: 3x - 4x = 3 - 4 → -x = -1 → x = 1 (has a solution)
-
4x + 3 = 3x + 3
- Rearranging gives: 4x - 3x = 3 - 3 → x = 0 (has a solution)
-
3x + 4 = 3x + 3
- Rearranging gives: 3x - 3x = 3 - 4 → 0 = -1 (contradictory, has no solution)
-
3x + 4 = 3x + 4
- This simplifies to a tautology (true for all x), so it has infinitely many solutions.
The correct answer is: 3x + 4 = 3x + 3, which has no solution.